Identifying Factors Contributing to Students’ Obstacles in Comprehending Recount Text - Samhudi, Samhudi (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This research was conducted to find out the difficulties faced by students in understanding recount text, and the factors that cause these difficulties. To obtain data in this study, the researcher used two data collection techniques, namely observation and interview. Observation is used to collect data in class during the teaching learning process. Interview is intended to identify the causes of the students’ obstacles in understanding recount text. There were 6 students at eleventh grade of SMAN 1 Nisam who were used as subjects in this research. 2 students who have high academic achievement, 2 medium and 2 low. The result showed that they had many difficulties in understanding recount text, both internal and external factors. The internal factor is the lack of motivation. Besides, they also have difficulties in understanding the sentence structure in recount text. In addition, they also lack of vocabulary mastery, it makes them difficult and take a long time to understand a text in English. The external factors that cause their difficulties in understanding English texts are the lack of attention from their parents towards their achievement, especially towards English achievement. They also only have a little time to learn and practice English at their home because they are busy with other activities. The lack of supporting facilities such as English reading materials and dictionaries, it is also one of the factors causing students’ difficulties in understanding recount text.